The Influence of Entrepreneurial Orientation on The Performance of Micro and Small Enterprises: The Mediating Role of Knowledge Management and Dynamic Capabilities - Imron Mashuri; Wahdiyat Moko (Politeknik Siber Cerdika Internasional, 2024)
This research discusses crucial aspects of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on comprehensive performance evaluation that includes financial and non-financial dimensions. Nevertheless, challenges such as the impact of the COVID-19 pandemic, limited entrepreneurial orientation, inadequate knowledge management, and difficulties adapting to rapid environmental changes have increased the rate of MSME closures in Indonesia. This study, involving 125 MSMEs in the Malang Raya region, examines the mediating role of knowledge management and dynamic capabilities in the relationship between entrepreneurial orientation and company performance. The results indicate that entrepreneurial orientation positively impacts company performance, knowledge management, and dynamic capabilities. However, knowledge management and dynamic capabilities do not significantly influence company performance, suggesting that they do not mediate between entrepreneurial orientation and company performance. Practically, these findings have significant implications for practitioners and policymakers seeking to enhance the performance of MSMEs in Indonesia. Recognizing the crucial role of entrepreneurial orientation in shaping positive company performance implies that fostering an entrepreneurial mindset is a key strategy. Nevertheless, considering the insignificant impact of knowledge management and dynamic capabilities on company performance, attention should be redirected towards alternative factors or strategies to address the unique challenges faced by Indonesian MSMEs. Policymakers can use these insights to design interventions targeting critical areas to create a conducive business environment for MSMEs in Indonesia.